Respuesta :

Answer:

Step-by-step explanation:

3/6 x 8

= ( 3 x 8 ) / 6

= 24 / 6

4/7 x 2

= ( 4 x 2 ) / 7

= 8 / 7

9/2 x 3

= ( 9 x 3 ) / 2

= 27 / 2

8/5 x 7

= ( 8 x 7 ) / 5

= 56 / 5

3/9 x 5

= ( 3 x 5 ) / 9

= 15/9

7/4 x 4

= ( 7 x 4 ) / 4

= 28 / 4

6/2 x 6

= ( 6 x 6 ) / 2

= 36 / 2

8/3 x 9

= ( 8 x 9 ) / 3

= 72 / 3

9/4 x 8

= ( 9 x 8 ) / 4

= 72 / 4

5/3 x 6

= ( 5 x 6 ) / 3

= 30 / 3

2/7 x 3

= ( 2 x 3 ) / 7

= 6 / 7

8/4 x 7

= ( 8 x 7 ) / 4

= 72 / 4

6/4 x 2

= ( 6 x 2 ) / 4

= 12 / 4